Cervical ossification of the posterior longitudinal ligament: factors affecting the effect of posterior decompression. (2nd January 2017) - Nishida, Norihiro; Kanchiku, Tsukasa; Kato, Yoshihiko; Imajo, Yasuaki; Suzuki, Hidenori; Yoshida, Yuichiro; Ohgi, Junji; Chen, Xian; Taguchi, Toshihiko
Abstract : Objective : Decompression procedures for cervical myelopathy of ossification of the posterior longitudinal ligament (OPLL) are anterior decompression with fusion, laminoplasty, and posterior decompression with fusion. Preoperative and postoperative stress analyses were performed for compression from hill-shaped cervical OPLL using 3-dimensional finite element method (FEM) spinal cord models. Methods : Three FEM models of vertebral arch, OPLL, and spinal cord were used to develop preoperative compression models of the spinal cord to which 10%, 20%, and 30% compression was applied; a posterior compression with fusion model of the posteriorly shifted vertebral arch; an advanced kyphosis model following posterior decompression with the spinal cord stretched in the kyphotic direction; and a combined model of advanced kyphosis following posterior decompression and intervertebral mobility. The combined model had discontinuity in the middle of OPLL, assuming the presence of residual intervertebral mobility at the level of maximum cord compression, and the spinal cord was mobile according to flexion of vertebral bodies by 5°, 10°, and 15°. Results : In the preoperative compression model, intraspinal stress increased as compression increased. In the posterior decompression with fusion model, intraspinal stress decreased, but partially persisted under 30% compression. In the advanced kyphosis model, intraspinal stress increased again. As anterior compression was higher, the stress increased more. In the advanced kyphosis  + intervertebral mobility model, intraspinal stress increased more than in the only advanced kyphosis model following decompression. Intraspinal stress increased more as intervertebral mobility increased. Conclusion : In high residual compression or instability after posterior decompression, anterior decompression with fusion or posterior decompression with instrumented fusion should be considered.